Magnesium alloy with composite low-absorption coating and preparation method thereof
By preparing a multi-layer gradient composite low-absorbent coating on a magnesium alloy matrix, the problems of uneven and insufficient density of the existing coating film are solved, efficient solar light reflection, corrosion resistance and stability are achieved, and spacecraft's needs for load weight reduction and heat dissipation are met.
Patent Information
- Application Number
- CN202510062988.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-06-03
AI Technical Summary
The surface coating of existing magnesium alloy substrates is uneven and the density is insufficient, resulting in poor corrosion resistance and reflection capabilities, which is difficult to meet the spacecraft's needs for load weight reduction, heat dissipation, corrosion resistance and wear resistance of precision devices.
A multi-layer gradient composite low-absorbent coating is used, including a magnesium alloy matrix, a microarc oxide layer and a magnetron sputtering deposition reflective film. The SiO2 film is deposited through a progressive gradient distribution of microarc oxidation Si, Zr, Zn salt layers and magnetron sputtering SiO2 film to form a composite coating with high density and low porosity.
The solar absorption ratio is significantly reduced by ≤0.2, improved corrosion resistance and stability, and can maintain film integrity in neutral salt spray test and vacuum thermal cycle test.
Smart Images

Figure HDA0005243455110000011 
Figure HDA0005243455110000012 
Figure HDA0005243455110000021
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of space functional coatings, and in particular to a magnesium alloy with a composite low-absorption coating and a preparation method thereof. Background Art
[0002] Magnesium alloy matrix materials have comprehensive properties such as light weight and high strength. Attaching functional coatings to the magnesium alloy substrate meets the requirements of the aerospace field for lightweight, high-strength, corrosion-resistant, and thermal control materials, and has received extensive attention. The low solar absorptance coating is a widely used space functional coating in spacecraft models. It can effectively reflect and scatter sunlight, and thus balance the energy absorption and radiation on the spacecraft surface through the thermal radiation performance of the coating, so that the cabin can reach the ideal operating temperature.
[0003] The new models of current spacecraft are developing rapidly, and their requirements for payloads are gradually becoming larger, more precise, and more thermal-controlled. Therefore, the new models of spacecraft have put forward higher requirements for payload weight reduction, heat dissipation, corrosion prevention, and wear resistance of precision devices. Therefore, a low solar absorptance coating can be prepared on the surface of the magnesium alloy to improve the reflection ability, corrosion and wear resistance, and thermal control ability of the lightweight magnesium alloy. However, the coating film layers manufactured by the existing processes at present are uneven and not dense, with insufficient corrosion resistance, and poor reflection ability and heat dissipation performance.
[0004] Therefore, exploring a low-absorption and corrosion-resistant wear-resistant coating attached to the surface of the magnesium alloy to prepare a material with a low solar absorptance and high corrosion and wear resistance is an urgent problem to be solved by those skilled in the art. Summary of the Invention
[0005] In view of this, the purpose of the present application is to provide a magnesium alloy with a composite low-absorption coating and a preparation method thereof, so that the coating of the magnesium alloy can reduce the solar absorptance ≤ 0.2 and significantly improve the corrosion resistance and stability.
[0006] To solve the above technical problems / achieve the above purpose or at least partially solve the above technical problems / achieve the above purpose, as the first aspect of the present application, there is provided a magnesium alloy with a composite low-absorption coating, including a magnesium alloy substrate, a micro-arc oxidation layer as a bottom coating, and a magnetron sputtering deposition reflection film as a top coating; the phases of the micro-arc oxidation layer include SiO 2 , ZrO 2 , ZnO and MgO, and the phases of the magnetron sputtering deposition reflection film include Si and SiO 2 .
[0007] Optionally, the micro-arc oxidation layer includes a first bottom coating, a second bottom coating, and a third bottom coating arranged in a stacked manner; the phases of the first bottom coating include SiO 2 and MgO, and the phases of the second bottom coating include ZrO2 , the phase of the third bottom coating includes ZnO.
[0008] Optionally, the thickness of the composite low-absorption coating is 60 - 80 μm, and the thickness of the magnetron sputtering deposited reflective film is 150 - 200 nm.
[0009] As the second aspect of the present application, a method for preparing the magnesium alloy is provided, including:
[0010] S1. Pretreat the magnesium alloy substrate;
[0011] S2. Perform micro-arc oxidation on the surface of the magnesium alloy substrate using a micro-arc oxidation electrolyte containing Si, Zr, and Zn to form a micro-arc oxidation layer as the bottom coating;
[0012] S3. Perform magnetron sputtering deposition on the magnesium alloy substrate using a silicon-containing target to form a magnetron sputtering deposited reflective film as the surface coating.
[0013] Optionally, step S2 includes:
[0014] S2.1. Perform micro-arc oxidation on the surface of the magnesium alloy substrate using a micro-arc oxidation electrolyte containing Si salt to form a first bottom coating;
[0015] S2.2. Perform micro-arc oxidation on the magnesium alloy substrate with the first bottom coating formed using a micro-arc oxidation electrolyte containing Zr salt to form a second bottom coating;
[0016] S2.3. Perform micro-arc oxidation on the magnesium alloy substrate with the first bottom coating formed using a micro-arc oxidation electrolyte containing Zn salt to form a third bottom coating.
[0017] Further optionally, the micro-arc oxidation electrolyte containing Si salt includes ammonium fluorosilicate, sodium silicate, potassium hydroxide, and water; the micro-arc oxidation electrolyte containing Zr salt includes ammonium zirconium fluoride, potassium dihydrogen phosphate, sodium silicate, phosphoric acid, and the pH value is 6 - 7; the micro-arc oxidation electrolyte containing Zn salt includes zinc orthotitanate, ammonium zirconium fluoride, potassium dihydrogen phosphate, sodium silicate, phosphoric acid, and the pH value is adjusted to 6 - 7.
[0018] Optionally, the working parameters of the micro-arc oxidation include:
[0019] The electrolyte temperature range is 15 - 35 °C, the forward voltage range is 350 - 700 V, the forward / duty cycle range is 10 - 20%, and the forward frequency range is 700 - 900 Hz.
[0020] Optionally, the working parameters of the magnetron sputtering include:
[0021] The deposition power is 200 - 350 W, the argon gas flow rate is 20 - 50 sccm, and the deposition time is 35 - 45 min.
[0022] The present application provides a magnesium alloy with a multi - layer gradient composite low - absorption coating, including a progressive gradient - distributed multi - layer stacked strong - reflection micro - arc oxidation layer and a magnetron - sputtered deposition reflection film. According to the synergistic effect of the multi - functional coating stack and the thin - film interference principle, a magnesium alloy composite coating with a series - connected and synergistically optimized multi - functional film layer is formed, which exhibits excellent comprehensive performance in terms of low absorption and corrosion resistance. In addition, this coating also has excellent stability and space - environment adaptability. Brief Description of the Drawings
[0023] Figure 1 The figure shows the appearance of the magnesium alloy multi - layer gradient composite low - absorption coating provided by Example 1 of the present application;
[0024] Figure 2 The figure shows the scanning electron microscope photograph of the magnesium alloy multi - layer gradient composite low - absorption coating provided by Example 1 of the present application;
[0025] Figure 3 The figure shows the appearance of the magnesium alloy multi - layer gradient composite low - absorption coating provided by Example 1 of the present application after 192 h of neutral salt spray test;
[0026] Figure 4 The figure shows the appearance of the magnesium alloy multi - layer gradient composite low - absorption coating provided by Comparative Example 1 of the present application;
[0027] Figure 5 The figure shows the appearance of the magnesium alloy multi - layer gradient composite low - absorption coating provided by Comparative Example 2 of the present application. Detailed Description of the Embodiments
[0028] The present application discloses a magnesium alloy with a composite low - absorption coating and its preparation method. Those skilled in the art can draw on the content of this article and appropriately modify the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present application. The products, processes, and applications described in the present application have been described through preferred embodiments, and those skilled in the art can obviously make changes or appropriate alterations and combinations to the processes and applications described in this article without departing from the content, spirit, and scope of the present application to implement and apply the technology of the present application. Obviously, the described embodiments are a part of the embodiments of the present application, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments in the present application without creative efforts belong to the scope of protection of the present application.
[0029] It should be noted that in this text, relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprising", "including" or any other variant thereof are intended to cover non-exclusive inclusion, such that a process, method, article or device comprising a series of elements not only includes those elements but also includes other elements not expressly listed, or further includes elements inherent to such process, method, article or device. Without further limitation, an element defined by the statement "comprising one..." does not exclude the presence of additional identical elements in the process, method, article or device comprising the element. At the same time, without conflict, the embodiments in the present application and the features in the embodiments may be combined with each other.
[0030] In the current surface treatment of magnesium and magnesium-lithium alloys, there are few processes with a solar absorptance performance that can reach below 0.2, and it is also difficult to simultaneously ensure a better level of corrosion resistance and long-term stability. Aiming at the defects of the current prior art, in the first aspect of the present application, a magnesium alloy with a composite low-absorption coating is provided, including a magnesium alloy substrate, a micro-arc oxidation layer as the bottom coating, and a magnetron sputtering deposition reflective film as the top coating; the phases of the micro-arc oxidation layer include SiO 2 、ZrO 2 、ZnO and MgO, and the phases of the magnetron sputtering deposition reflective film include Si and SiO 2 .
[0031] The present application adopts a method of gradually connecting and synergistically optimizing the solar absorptance with multiple functional film layers. By preparing a combined composite coating with a micro-arc oxidation Si salt layer, Zr salt layer, and Zn salt layer with a gradually gradient distribution of reflection ability as the inner layer and a magnetron sputtering deposition Si film as the surface layer, a nano-micron scale metal oxide with strong sunlight reflection, high density, low porosity, self-sealing pores, and a gradually gradient distribution of reflection ability is constructed to improve the reflection and scattering ability of the magnesium alloy substrate to different spectral energies of sunlight. By introducing elements such as Si, Zr, Zn, and O into the gradually stacked micro-arc oxidation layer and the outer surface magnetron sputtering deposition film of the multi-functional coating, the reflectivity of the magnesium alloy substrate is increased so that the solar absorptance ≤ 0.20, the neutral salt spray resistance ≥ 192 h, and the film layer does not fall off after 100 times of -196°C to 100°C vacuum thermal cycle tests.
[0032] In some embodiments of the present application, the micro-arc oxidation layer includes a first bottom coating, a second bottom coating, and a third bottom coating arranged in a stacked manner; the three coatings are stacked in sequence; the phases of the first bottom coating include SiO 2and MgO, and the phases of the second bottom coating include ZrO 2 , and the phases of the third bottom coating include ZnO. The three-layer micro-arc oxidation layer adopts a progressive gradient distribution and multi-layer stacking to synergistically enhance the reflection ability of different spectral energies of sunlight. The Si layer deposited on the subsequent surface layer further enhances the reflection ability of the composite coating, thereby reducing the solar absorptance of the coating and enhancing the corrosion resistance and long-term stability of the coating.
[0033] In some embodiments of the present application, the thickness of the composite low-absorption coating is 60-80 μm, and the thickness of the magnetron sputtering deposited reflective film is 150-200 nm. Among them, the thickness of the first bottom coating is 5-10 μm, the thickness of the second bottom coating is 20-30 μm, and the thickness of the third bottom coating is 30-40 μm. The first bottom coating is for improving the conductivity of the substrate and should not be too thick; the second and third bottom coatings should not be too thin, otherwise the film layer on the substrate surface will have uneven color, unevenness and defects, ultimately affecting the low-absorption performance.
[0034] In the second aspect of the present application, a method for preparing the magnesium alloy is provided, including:
[0035] S1. Pretreating the magnesium alloy substrate;
[0036] S2. Performing micro-arc oxidation on the surface of the magnesium alloy substrate with a micro-arc oxidation electrolyte containing Si, Zr, and Zn to form a micro-arc oxidation layer as the bottom coating;
[0037] S3. Performing magnetron sputtering deposition on the magnesium alloy substrate with a silicon-containing target to form a magnetron sputtering deposited reflective film as the surface coating.
[0038] In some embodiments of the present application, the pretreatment in step S1 includes cleaning and roughening, where the roughening includes one or more of sandblasting, sandpaper polishing, pickling, alkali washing, and activation, so that the roughness of the magnesium alloy substrate after roughening is not less than 3.2.
[0039] In some embodiments of the present application, step S2 includes:
[0040] S2.1. Performing micro-arc oxidation on the surface of the magnesium alloy substrate with a micro-arc oxidation electrolyte containing Si salt to form a first bottom coating;
[0041] S2.2. Performing micro-arc oxidation on the magnesium alloy substrate with the first bottom coating formed with a micro-arc oxidation electrolyte containing Zr salt to form a second bottom coating;
[0042] S2.3. Performing micro-arc oxidation on the magnesium alloy substrate with the first bottom coating formed with a micro-arc oxidation electrolyte containing Zn salt to form a third bottom coating.
[0043] In some other embodiments of the present application, the micro-arc oxidation electrolyte containing Si salt includes ammonium fluorosilicate, sodium silicate, potassium hydroxide and water; specifically, the micro-arc oxidation electrolyte containing Si salt includes 6-9 g / L of ammonium fluorosilicate, 7-9 g / L of sodium silicate, 7-10 g / L of potassium hydroxide and pure water. In some other embodiments of the present application, the micro-arc oxidation electrolyte containing Si salt is filled into an electrolytic cell, with a magnesium alloy substrate as the anode and a stainless steel plate as the cathode, and a direct current is applied to generate micro-arc discharge, and the micro-arc oxidation process is used to process the substrate for 4-8 minutes.
[0044] In some other embodiments of the present application, the micro-arc oxidation electrolyte containing Zr salt includes ammonium fluozirconate, potassium dihydrogen phosphate, sodium silicate, phosphoric acid, and the pH value is 6-7; specifically, the micro-arc oxidation electrolyte containing Zr salt includes 5-10 g / L of ammonium fluozirconate, 4-8 g / L of potassium dihydrogen phosphate, 5-7 g / L of sodium silicate, 3-6 g / L of phosphoric acid, and the pH value is 6-7. In some other embodiments of the present application, the micro-arc oxidation electrolyte containing Zr salt is filled into an electrolytic cell, and the magnesium alloy substrate with a Si salt micro-arc oxidation layer obtained in S2.1 is used as the anode, with a stainless steel plate as the cathode, and a direct current is applied to generate micro-arc discharge, and the micro-arc oxidation process is used to process the sample for 20-30 minutes.
[0045] In some other embodiments of the present application, the micro-arc oxidation electrolyte containing Zn salt includes zinc orthotitanate, ammonium fluozirconate, potassium dihydrogen phosphate, sodium silicate, phosphoric acid, and the pH value is adjusted to 6-7; specifically, the micro-arc oxidation electrolyte containing Zn salt includes 4-7 g / L of zinc orthotitanate, 3-6 g / L of ammonium fluozirconate, 4-8 g / L of potassium dihydrogen phosphate, 5-7 g / L of sodium silicate, 3-6 g / L of phosphoric acid, and the pH value is 6-7. In some other embodiments of the present application, the micro-arc oxidation electrolyte containing Zn salt is filled into an electrolytic cell, and the magnesium alloy substrate with a Zr salt micro-arc oxidation layer obtained in S2.2 is used as the anode, with a stainless steel plate as the cathode, and a direct current is applied to generate micro-arc discharge, and the micro-arc oxidation process is used to process the sample for 30-40 minutes.
[0046] In some embodiments of the present application, the working parameters of the micro-arc oxidation include:
[0047] The electrolyte temperature range is 15-35 °C, the forward voltage range is 350-700 V, the forward / duty ratio range is 10-20%, and the forward frequency range is 700-900 Hz.
[0048] In some other embodiments of the present application, the working parameters of the micro-arc oxidation in step S2.1 include:
[0049] The temperature range of the electrolyte is 15 - 35 °C, the forward voltage range is 350 - 450 V, the forward / duty cycle range is 10 - 20%, and the forward frequency range is 700 - 900 Hz;
[0050] The working parameters of the micro-arc oxidation in step S2.2 include:
[0051] The temperature range of the electrolyte is 15 - 35 °C, the forward voltage range is 500 - 650 V, the forward / duty cycle range is 10 - 20%, and the forward frequency range is 700 - 900 Hz;
[0052] The working parameters of the micro-arc oxidation in step S2.3 include:
[0053] The temperature range of the electrolyte is 15 - 35 °C, the forward voltage range is 500 - 700 V, the forward / duty cycle range is 10 - 20%, and the forward frequency range is 700 - 900 Hz.
[0054] In some embodiments of the present application, after the micro-arc oxidation is completed, the magnesium alloy substrate is cleaned and dried; in some other embodiments of the present application, after the micro-arc oxidation process ends, the magnesium alloy substrate is taken out, rinsed with ultrapure water, and then the magnesium alloy is placed in an oven, the oven temperature is set to 50 - 70 °C, and dried for 4 - 8 h.
[0055] In some embodiments of the present application, the working parameters of the magnetron sputtering include:
[0056] The deposition power is 200 - 350 W, the argon gas flow rate is 20 - 50 sccm, and the deposition time is 35 - 45 min.
[0057] In some other embodiments of the present application, the magnesium alloy substrate coated with the Zn salt micro-arc oxidation layer obtained in S2.3 is placed in the cavity of the magnetron sputtering deposition equipment, a radio frequency power supply is selected, the target is a single-element SiO 2 plate, the magnetron sputtering deposition power is 200 - 350 W, the argon gas flow rate is 20 - 50 sccm, and the deposition time is 35 - 45 min. After the deposition process ends, the magnesium alloy substrate is taken out to obtain the fourth layer of magnetron sputtering deposited SiO 2 reflective film.
[0058] In each group of comparative experiments provided in the present application, unless otherwise specified, except for the differences pointed out in each group, other experimental conditions, materials, etc. are kept consistent for comparability. The experimental materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.
[0059] The performance detection methods involved in the specific embodiments of the present application are as follows:
[0060] Solar absorptance test: Refer to "GJB 2502.2-2006 Test Methods for Thermal Control Coatings of Spacecraft - Part 2: Solar Absorptance Test".
[0061] Neutral salt spray test: The test of neutral salt spray is carried out with reference to the conditions given in "GB 2423.17-2008 Environmental Testing for Electric and Electronic Products - Part 2: Test Methods - Test Ka: Salt Spray", and according to the detection standard, the neutral salt spray resistance time of the samples obtained in each example and comparative example is determined.
[0062] Vacuum thermal cycle test: Refer to "GJB 2502.8-2015 Test Methods for Thermal Control Coatings of Spacecraft - Part 8: Thermal Cycle Test".
[0063] The following further describes a magnesium alloy with a composite low-absorption coating and its preparation method provided by this application.
[0064] Example 1:
[0065] The following treatments are carried out on the MB15 magnesium alloy substrate:
[0066] 1. Wipe the magnesium alloy plate with an organic solvent and ethanol to remove the surface contaminants of the magnesium alloy substrate;
[0067] 2. The magnesium alloy substrate obtained in step 1 is pretreated and roughened by sandpaper grinding, alkali washing, acid washing, activation and other methods, so that the roughness of the magnesium alloy substrate reaches 3.2 after roughening.
[0068] 3. The magnesium alloy substrate obtained in step 2 is subjected to micro-arc oxidation treatment. The electrolyte formula and operating conditions are as follows:
[0069] 3.1: Prepare the Si salt electrolyte required for preparing the micro-arc oxidation layer, and prepare ammonium fluorosilicate (8 g / L), sodium silicate (8 g / L), and potassium hydroxide (8 g / L) at the specified concentrations, and adjust the pH value to 6.5 to obtain the required Si salt electrolyte;
[0070] 3.2: Fill the electrolyte obtained in 3.1 into the electrolytic cell, use the magnesium alloy part obtained in step 2 as the anode, use a stainless steel plate as the cathode, apply direct current to generate micro-arc discharge, and process the sample with the micro-arc oxidation process for 7 minutes. The temperature range of the electrolyte is controlled at 16-32 °C, the forward voltage is 420 V, the forward / duty cycle is 15%, and the forward frequency is 800 Hz to obtain the first layer of Si salt micro-arc oxidation layer;
[0071] 3.3: Prepare the Zr salt electrolyte required for the micro-arc oxidation layer. Prepare chemicals such as ammonium hexafluorozirconate (7 g / L), potassium dihydrogen phosphate (6 g / L), sodium silicate (6 g / L), and phosphoric acid (4 g / L) at the specified concentrations, and adjust the pH value to 6.5 to obtain the required Zr salt electrolyte;
[0072] 3.4: Fill the electrolyte obtained in 3.3 into the electrolytic cell. Use the magnesium alloy part coated with the Si salt micro-arc oxidation layer obtained in 3.2 as the anode, use a stainless steel plate as the cathode, apply direct current to generate micro-arc discharge, and process the sample using the micro-arc oxidation process for 25 minutes. The requirements for the electrolyte temperature are 25 °C, the positive voltage is 600 V, the positive / duty cycle is 15%, and the positive frequency is 800 Hz to obtain the second layer of Zr salt micro-arc oxidation layer;
[0073] 3.5: Prepare the Zn salt electrolyte required for the micro-arc oxidation layer. Prepare chemicals such as zinc orthotitanate (powder size 300 nm, 6 g / L), ammonium hexafluorozirconate (4 g / L), potassium dihydrogen phosphate (6 g / L), sodium silicate (6 g / L), and phosphoric acid (4 g / L) at the specified concentrations, and adjust the pH value to 6.5 to obtain the required Zn salt electrolyte;
[0074] 3.6: Fill the electrolyte obtained in 3.5 into the electrolytic cell. Use the magnesium alloy part coated with the Zr salt micro-arc oxidation layer obtained in 3.4 as the anode, use a stainless steel plate as the cathode, apply direct current to generate micro-arc discharge, and process the sample using the micro-arc oxidation process for 35 minutes. The requirements for the electrolyte temperature are 25 °C, the positive voltage is 650 V, the positive / duty cycle is 15%, and the positive frequency is 800 Hz;
[0075] 3.7: After the micro-arc oxidation process is completed, take out the sample, rinse it with ultrapure water, then put the sample into an oven, set the oven temperature to 60 °C, and dry it for 4 hours to finally obtain the third layer of Zn salt micro-arc oxidation layer.
[0076] 4. Place the magnesium alloy part coated with the Zn salt micro-arc oxidation layer obtained in 3.7 into the cavity of the magnetron sputtering deposition equipment. Select a radio frequency power supply, use a single-element SiO 2 plate as the target, the magnetron sputtering deposition power is 300 W, the argon gas flow rate is 30 sccm, and the deposition time is 40 minutes. After the deposition process is completed, take out the sample to obtain the fourth layer of magnetron sputtered SiO 2 film. Finally, the magnesium alloy multi-layer gradient composite low-absorption coating is prepared.
[0077] 5. Detection of the magnesium alloy multi-layer gradient composite low-absorption coating
[0078] Test the absorption performance and corrosion resistance of the multi-layer gradient composite low-absorption coating on magnesium alloy. Its solar absorptance is 0.18, and it can withstand neutral salt spray for 192 h. After 100 vacuum thermal cycle tests from -196°C to 100°C, the coating film does not peel off.
[0079] Use a thickness gauge to measure the thickness of the prepared multi-layer gradient composite low-absorption coating on magnesium alloy. The thickness of the multi-layer gradient composite low-absorption coating on magnesium alloy is 75 μm, among which the thickness of the magnetron sputtering deposition film of the surface coating is 200 nm.
[0080] See Figure 1 , Figure 1 For the appearance diagram of the multi-layer gradient composite low-absorption coating on magnesium alloy in Example 1, it can be seen from the figure that the surface color of the composite coating is uniform, flat, smooth and without defects.
[0081] See Figure 2 , Figure 2 For the scanning electron microscope photo of the multi-layer gradient composite low-absorption coating on magnesium alloy in Example 1, it can be seen from the figure that the surface of the composite coating is in a highly dense state and has an ultra-low porosity. No obvious cracks are found in the coating film, and the surface of the coating film shows layered alternating growth, indicating that the multi-layer gradient composite low-absorption coating on magnesium alloy has the characteristics of low porosity and high density.
[0082] See Figure 3 , Figure 3 For the appearance diagram of the multi-layer gradient composite low-absorption coating on magnesium alloy in Example 1 after 192 h of neutral salt spray test, it can be seen from the figure that after 192 h of neutral salt spray test, the surface of the composite coating is smooth and flat, and no corrosion phenomenon is found, indicating that the multi-layer gradient composite low-absorption coating on magnesium alloy has good corrosion resistance.
[0083] Example 2:
[0084] On the basis of Example 1, the following adjustments are made in Example 2:
[0085] The magnesium alloy substrate was treated according to the steps of Example 1. When preparing the Si salt electrolyte required for the micro-arc oxidation layer, ammonium hexafluorosilicate (6 g / L), sodium silicate (7 g / L), and potassium hydroxide (7 g / L) were prepared at the specified concentrations, and the pH value was adjusted to 6.5. The voltage of micro-arc oxidation was 350 V, and the processing time was 5 min. When preparing the Zr salt electrolyte required for the micro-arc oxidation layer, ammonium hexafluorozirconate (5 g / L), potassium dihydrogen phosphate (4 g / L), sodium silicate (5 g / L), phosphoric acid (3 g / L), etc. were prepared at the specified concentrations, and the pH value was adjusted to 6.5. The voltage of micro-arc oxidation was 550 V, and the processing time was 20 min. When preparing the Zn salt electrolyte required for the micro-arc oxidation layer, zinc orthotitanate (powder size 300 nm, 4 g / L), ammonium hexafluorozirconate (3 g / L), potassium dihydrogen phosphate (4 g / L), sodium silicate (5 g / L), phosphoric acid (3 g / L), etc. were prepared at the specified concentrations, and the pH value was adjusted to 6.5. The voltage of micro-arc oxidation was 600 V, and the processing time was 30 min. The magnetron sputtering deposition power was 200 W, the argon gas flow rate was 20 sccm, and the deposition time was 35 min.
[0086] The absorption performance and corrosion resistance of the test sample were tested. Its solar absorptance was 0.20, the neutral salt spray resistance was 192 h, and the film layer did not peel off after 100 vacuum thermal cycle tests from -196 °C to 100 °C.
[0087] A thickness gauge was used to test the thickness of the prepared sample, and the thickness of the sample was 60 μm. The surface color of the composite coating was uniform, flat, smooth, and free of defects; the surface was in a highly dense state and had an ultra-low porosity. No obvious cracks were found in the film layer, and the surface of the film layer showed layered alternating growth, indicating that the magnesium alloy multi-layer gradient composite low-absorption coating had the characteristics of low porosity and high density.
[0088] Example 3:
[0089] On the basis of Example 1, the following adjustments were made in Example 3:
[0090] The magnesium alloy substrate was treated according to the steps of Example 1. When preparing the Si salt electrolyte for the micro-arc oxidation layer, ammonium fluorosilicate (9 g / L), sodium silicate (9 g / L), and potassium hydroxide (8 g / L) were prepared at the specified concentrations, and the pH value was adjusted to 6.5. The voltage of micro-arc oxidation was 450 V, and the processing time was 10 min. When preparing the Zr salt electrolyte for the micro-arc oxidation layer, ammonium fluorozirconate (10 g / L), potassium dihydrogen phosphate (8 g / L), sodium silicate (7 g / L), phosphoric acid (6 g / L), etc. were prepared at the specified concentrations, and the pH value was adjusted to 6.5. The voltage of micro-arc oxidation was 650 V, and the processing time was 30 min. When preparing the Zn salt electrolyte for the micro-arc oxidation layer, zinc orthotitanate (powder size 400 nm, 7 g / L), ammonium fluorozirconate (6 g / L), potassium dihydrogen phosphate (8 g / L), sodium silicate (7 g / L), phosphoric acid (6 g / L), etc. were prepared at the specified concentrations, and the pH value was adjusted to 6.5. The voltage of micro-arc oxidation was 700 V, and the processing time was 40 min. The magnetron sputtering deposition power was 350 W, the argon gas flow rate was 50 sccm, and the deposition time was 45 min.
[0091] The absorption performance and corrosion resistance of the test specimens were tested. The solar absorptance was 0.19, the neutral salt spray resistance was 192 h, and the film layer did not peel off after 100 vacuum thermal cycle tests from -196 °C to 100 °C.
[0092] A thickness gauge was used to measure the thickness of the prepared specimens, and the thickness of the specimens was 80 μm. The surface color of the composite coating was uniform, flat, smooth, and free of defects; the surface was in a highly dense state and had an ultra-low porosity. No obvious cracks were found in the film layer, and the film layer surface showed layered alternating growth, indicating that the magnesium alloy multi-layer gradient composite low-absorption coating had the characteristics of low porosity and high density.
[0093] Comparative Example 1:
[0094] Based on Example 1, the following adjustments were made in Comparative Example 1:
[0095] The magnesium alloy substrate was treated according to the steps of Example 1, without performing steps 3.3 to 4. That is, a Si salt micro-arc oxidation layer was prepared on the magnesium alloy substrate by the micro-arc oxidation process, and the specimens were obtained after drying. See Figure 4 , Figure 4 is the appearance diagram of the specimen of Comparative Example 1, and the color is darker.
[0096] The absorption performance and corrosion resistance of the test specimens were tested. The solar absorptance was 0.35, and the neutral salt spray resistance was 92 h. Compared with the performance of the examples of the present application, there was an obvious decrease. A thickness gauge was used to measure the thickness of the prepared specimens, and the thickness of the specimens was 8 μm.
[0097] Comparative Example 2:
[0098] On the basis of Example 1, the following adjustments are made to Comparative Example 2:
[0099] The magnesium alloy substrate is treated according to the steps of Example 1, without performing steps 3.1 to 3.4 and step 4. That is, a Zn salt micro-arc oxidation layer is prepared on the magnesium alloy substrate by micro-arc oxidation process, and the sample is obtained after drying. See Figure 5 , the surface color of the composite coating is uneven and relatively deep, uneven and defective.
[0100] The absorption performance and corrosion resistance of the test sample are tested. Its solar absorptance is 0.26, and the neutral salt spray resistance is 92 h. Compared with the performance of the embodiment of the present application, there is an obvious decrease. The thickness of the prepared sample is measured by a thickness gauge, and the thickness of the sample is 25 μm.
[0101] The above are only specific embodiments of the present application, enabling those skilled in the art to understand or implement the present application. Various modifications to these embodiments will be obvious to those skilled in the art. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A magnesium alloy with a composite low-absorption coating, characterized in that: The invention comprises a magnesium alloy substrate, a micro-arc oxidation layer as a bottom coating and a magnetron sputtering deposited reflective film as a top coating; the phases of the micro-arc oxidation layer comprise SiO2, ZrO2, ZnO and MgO, and the phases of the magnetron sputtering deposited reflective film comprise Si and SiO2.
2. The magnesium alloy according to claim 1, characterized in that The micro-arc oxidation layer includes a first primer layer, a second primer layer and a third primer layer which are stacked; the first primer layer includes SiO2 and MgO, the second primer layer includes ZrO2, and the third primer layer includes ZnO.
3. The magnesium alloy according to claim 1, characterized in that The thickness of the composite low-absorption coating is 60-80 μm, and the thickness of the magnetron sputtering deposited reflective film is 150-200 nm.
4. The method for preparing the magnesium alloy according to claim 1, characterized in that: include: S1. Pretreatment of the magnesium alloy substrate; S2. Micro-arc oxidation is performed on the surface of the magnesium alloy substrate using a micro-arc oxidation electrolyte containing Si, Zr and Zn to form a micro-arc oxidation layer as a primer; S3. Performing magnetron sputtering deposition on the magnesium alloy substrate with a silicon-containing target material to form a magnetron sputtering deposition reflective film as a top coating.
5. The preparation method according to claim 4, characterized in that: Step S2 includes: S2.1, performing micro-arc oxidation on the surface of the magnesium alloy substrate using a micro-arc oxidation electrolyte containing Si salt to form a first primer layer; S2.2, using a micro-arc oxidation electrolyte containing a Zr salt to micro-arc oxidize the magnesium alloy substrate on which the first primer layer is formed, to form a second primer layer; S2.
3. Micro-arc oxidation is performed on the magnesium alloy substrate forming the first primer layer using a micro-arc oxidation electrolyte containing Zn salt to form a third primer layer.
6. The preparation method according to claim 5, characterized in that: The Si salt-containing micro-arc oxidation electrolyte comprises ammonium fluorosilicate, sodium silicate, potassium hydroxide and water.
7. The preparation method according to claim 5, characterized in that: The micro-arc oxidation electrolyte containing Zr salt comprises ammonium fluorozirconate, potassium dihydrogen phosphate, sodium silicate and phosphoric acid, and has a pH value of 6-7.
8. The preparation method according to claim 5, characterized in that: The Zn salt-containing micro-arc oxidation electrolyte comprises zinc titanate, ammonium fluorozirconate, potassium dihydrogen phosphate, sodium silicate and phosphoric acid, and the pH value is adjusted to 6-7.
9. The preparation method according to claim 4 or 5, characterized in that: The working parameters of the micro-arc oxidation include: The electrolyte temperature range is 15-35° C., the forward voltage range is 350-700 V, the forward / duty ratio range is 10-20%, and the forward frequency range is 700-900 Hz.
10. The preparation method according to claim 4, characterized in that: The operating parameters of the magnetron sputtering include: The deposition power is 200-350 W, the argon gas flow rate is 20-50 sccm, and the deposition time is 35-45 min.
Citation Information
Cited By
White micro-arc oxidation film on surface of magnesium alloy and preparation method of white micro-arc oxidation film
CN121538702A